The Effect of an App‐Based Multimodal Cancer Rehabilitation Programme on Sense of Coherence of Women With Gynaecological Cancer: Study Protocol for a Randomised Controlled Trial - Ka Ming Chow; Carmen Wing Han Chan; Alexandra Leigh McCarthy; Jiemin Zhu; Kai Chow Choi; Ka Yi Siu; Alice Wai Yi Leung (Nursing Open, 2025)
ABSTRACT Aim To investigate the effects and cost‐effectiveness of an app‐based multimodal cancer rehabilitation programme promoting sense of coherence for women treated for gynaecological cancer, and to understand participants' experience of the programme. Design An assessor‐blinded, concurrent mixed‐method randomised controlled trial. Methods Gynaecological cancer patients (N = 160) will be recruited and randomly assigned to an intervention group (n = 80) or an attention control group (n = 80). The intervention group will receive the multimodal cancer rehabilitation programme over 12 weeks, in which they will access a Hong Kong‐adapted version of the Australian Women's Wellness after Cancer Programme via a mobile application, plus three virtual individual counselling sessions and reminder phone calls. The attention control group will receive usual care plus telephone calls to deliver general greetings. The outcome variables of sense of coherence, cancer‐specific distress, health‐promoting behaviours and health‐related quality of life (HRQoL) will be measured at baseline (T0), on the completion of the programme (T1) and 12 weeks after intervention completion (T2). HRQoL of the participants will be further reassessed every 3 months from T2 till 12‐month post‐intervention to evaluate cost‐effectiveness. Semi‐structured interviews will explore the participants' experience and perceptions of the programme. This study will adhere to the CONSORT‐EHEALTH checklist. Conclusion This study will offer the first empirical evidence regarding the effectiveness of the multimodal cancer rehabilitation programme in enhancing sense of coherence, reducing cancer‐specific distress, promoting positive lifestyle changes, and improving quality of life for women treated for gynaecological cancer. Implications for the Profession and/or Patient Care Women treated for gynaecological cancer experience unmet rehabilitation needs, yet healthcare professionals might not have the time or resources to meet these needs after intensive treatment is complete. This digital intervention could be incorporated into routine service delivery and adapted to other female cancer groups to improve patient outcomes. Reporting Method This protocol adhered to the SPRIT 2013 statement. Patient or Public Contribution None. Trial Registration ISRCTN registry number: ISRCTN17629214 (registered in November 2023)